The Relevance of Islamic Education Evaluation to Students' Spiritual Attitudes at SMKN 3 Cimahi - Siti Nuraeni; Yanti Sapitri; Huriyatul Kamilah; Opik Taupik Kurahman (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the relevance of the Islamic Education (PAI) evaluation system to the development of students’ spiritual attitudes at SMKN 3 Cimahi. The main focus is to understand how the assessment practices implemented by teachers support the strengthening of faith, piety, and moral values in students’ daily lives. This research employs a qualitative approach through classroom observations, document analysis, and interviews with Islamic Education teachers and several students as supporting informants. The findings indicate that PAI evaluation still predominantly measures cognitive abilities through written tests and academic assessments. Although spiritual attitude assessments, such as the discipline of worship, moral behavior, and honesty, have been applied, they are not yet optimal due to limited instruments and the absence of consistent monitoring. Nevertheless, the habituation of religious practices and teachers’ role-modeling continue to have a positive impact on students’ spiritual development. This study suggests strengthening affective and practical worship assessments in a more structured manner, as well as encouraging greater involvement of the entire school community so that spiritual evaluation does not become merely a formality. Islamic Education evaluation is expected to fully reflect the aims of Islamic education, which include nurturing intellectually capable students with noble character.